QCA Analysis of Factors Contributing to Poor Policing Activities In Mining And Quarrying In Indonesia - Suhendarwan, Bhakti; Fauzi, Akhmad; Mulatsih, Sri; Juanda, Bambang (Green Publisher Indonesia, 2025)
The paradox of natural resource management is the finding that is the basis for this study. The paradox shows that areas that depend on natural resource management, such as mining and quarrying, have lower scores in supervision, partnerships, and law enforcement scores than areas with no income from mining and quarrying activities. The Qualitative, quantitative comparative analysis (QCA) method is used to find the pathway that causes the paradox in each research area; QCA will provide a general pathway as to why an area has different characteristics from other regions even though they have identical scores and indicators in statistical measurements. As the result, The qualitative comparative analysis (QCA) shows that regional areas with a high composite index score have certain pathway characteristics, such as the high integrity of public employees and the low level of corrupt behavior in the area.